EVALUATING THE EFFECTIVENESS OF PICTURE BOOKS IN INTRODUCING ENGLISH TO EARLY CHILDHOOD LEARNERS: A CASE STUDY IN SOUTH GARUT - Ratnasari , Resty; Nur Fajriah, Yustika; Rahim , Norani Abd (English Education and Applied Linguistics Journal (EEAL Journal), 2024)
This study explores the effectiveness of using picture books as a medium to introduce English to early childhood learners at an Early Childhood Education School in South Garut, West Java, Indonesia. This qualitative research employed a case study approach, involving four sessions conducted over two weeks, with a focus on assessing the impact of picture books on English language acquisition among 20 students aged 5-6 years. The research involved a systematic introduction of English through picture books depicting various fruits. Initial observations indicated limited student engagement, but participation increased significantly in subsequent sessions, with nearly 90% of the children actively involved by the third and fourth meetings. The study highlights that picture books, as a novel and age-appropriate tool, can effectively enhance early language learning by capturing children's interest and facilitating their understanding of new vocabulary. Findings suggest that picture books not only improve language skills but also foster a positive learning environment by aligning with children's preferences for visual stimuli. The successful implementation of this method underscores the potential of picture books in early childhood education, advocating for their use in introducing English and possibly other subjects.